2021
DOI: 10.3389/frvir.2021.670909
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality in the Teaching of Challenging Concepts in Virology, Cell Culture and Molecular Biology

Abstract: The rapidly expanding biotechnology sector horizon is expected to create a surge in demand for expertise underpinning cell and gene therapies, which are recognized as the next generation of medicines. New and innovative approaches to implement active and performative learning in the Molecular Life Sciences are required to support this and to address limitations associated with traditional “front of class” lectern delivery of challenging, three dimensional molecular concepts. Therefore, an immediate need exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…A pilot survey (n = 22) completed by students taking a microbiology module at UCC prior to the codesign of the bespoke VR simulations showed that (a) 88% of respondents could see potential in the use of digital technologies, (b) 79% of respondents indicated that they learn well through visual modules and, (c) 15% of respondents declared competency in the use of VR technologies. Together, these data highlight the huge potential for VR integration into molecular biology curricula [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pilot survey (n = 22) completed by students taking a microbiology module at UCC prior to the codesign of the bespoke VR simulations showed that (a) 88% of respondents could see potential in the use of digital technologies, (b) 79% of respondents indicated that they learn well through visual modules and, (c) 15% of respondents declared competency in the use of VR technologies. Together, these data highlight the huge potential for VR integration into molecular biology curricula [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of I-VR brings many challenges with respect to Universal Design for Learning (UDL) and requires careful attention to detail in the early design phase (Reen et al . 2021 ). Users can experience difficulty with the technology handling (hardware and software), interpretation of color schemes, audio aspects and the spatial nature of the structures represented.…”
Section: Resultsmentioning
confidence: 99%
“…While the use of immersive virtual reality (I-VR) in Higher Education remains an area of active investigation, particularly with respect to accessing challenging molecular or cellular concepts (Reen et al . 2021 ), there is growing evidence of the importance of active learning in pedagogical design (Espinosa et al . 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because it provides learners with the ability to practice in environments that more closely mimic real-life situations, virtual reality (VR) provides a superior approach for simulating complex scenarios such as MCIs. [17][18][19] VR systems are reusable and portable, and once developed they can be cost-effective in comparison to conventional training methods. 10,20 They can be designed to include automated, unbiased assessment of the trainee's performance, provide real-time feedback, and be customized to provide variable levels of difficulty or interchangeable scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Because it provides learners with the ability to practice in environments that more closely mimic real‐life situations, virtual reality (VR) provides a superior approach for simulating complex scenarios such as MCIs 17–19 . VR systems are reusable and portable, and once developed they can be cost‐effective in comparison to conventional training methods 10,20 .…”
Section: Introductionmentioning
confidence: 99%